The epidemiology of wrist and hand injury in two hospitals in Jerusalem: substantial differences between population subgroups - Shai Luria; Daniel Talmud; Ido Volk; Meir Liebergall; Ronit Calderon-Margalit (BMC, 2019)
Abstract Background Wrist and hand injuries are common and constitute a major economic burden. General injury prevention programs have failed to demonstrate a decrease in injury rates. We hypothesized that there are differences in injury patterns in culturally diverse subpopulations of a metropolitan area treated within the same medical system, which may partly explain the difficulties associated with injury prevention. Methods We conducted a survey of patients admitted to emergency departments of two hospitals in Jerusalem for wrist and hand injuries during a 3 month period. Patients were asked to complete a questionnaire regarding demographic data, injury type and mechanism. Injury type and mechanism were then compared for age, gender, level of education and degree of religiosity. Results The questionnaire was completed by 799 patients (response rate 62%; 75% male; average age 27). Thirty-one percent reported they were injured at work, 33% at home and 36% during leisure activities. Data analysis showed that several subpopulations were found to be at risk as compared to their corresponding groups and relative proportion in the overall population of the city. These included contusions after falls in non-ultra-Orthodox Jewish women aged 65 years and over, crush injuries in ultra-Orthodox Jews under the age of 10 (53% vs. 14% for non ultra-Orthodox Jews, respectively) and Muslim teens. Muslims were injured more, especially at work, in comparison to their relative proportion in the population as a whole. Conclusion Different subpopulations at risk and different injury patterns of wrist and hand injuries were found in this culturally heterogeneous population. Awareness of these differences may be the first step when designing specific injury prevention programs in a culturally diverse population. A combined effort of community leaders and government agencies is needed to deal with the specific populations at risk, although legislation may be needed to limit some of the risks such as teens and specific work related hazards and exposures.